Tools and Algorithms for the Construction and Analysis of Systems: 31st International Conference, TACAS 2025, Held as Part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025, Hamilton, ON, Canada, May 3–8, 2025, Proceedings, Part II (Lecture Notes in Computer Science, 2025)
The open access book set LNCS 15696, 15697 and 15698 constitutes the proceedings of the 31st International Conference on Tools and Algorithms for the Construction and Analysis of Systems, TACAS 2025, which was held as part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025, during May 3-8, 2025, in Hamilton, Canada. The 46 papers presented were carefully reviewed and selected from 148 submissions. The proceedings also include 14 papers from the Software Verification competition which was held as part of TACAS. The papers were organized in topical sections as follows: Part I: Program analysis, ATP and rewriting; model checking; LTL; verification; Part II: SAT and SMT solving; proofs and certificates; synthesis; equivalence checking; games; Part III: Verification; quantum and GPU; 14th Competition on Software Verification, SV-COMP 2025.